Associations of hypertension burden on subsequent dementia: a population-based cohort study - Hyunjean Jung (Nature Portfolio, 2021)
Abstract In this nationwide cohort study, we assessed the effects of hypertension burden and blood pressure (BP) control on dementia in different age subgroups. From the Korean National Health Insurance Service-Health Screening cohort from January 1, 2005 to December 31, 2013, we enrolled 428,976 subjects aged 40–79 years without previous diagnosis of dementia or stroke. During a mean follow-up of 7.3 ± 1.5 years, 9435 (2.2%) were diagnosed with dementia. Per 10 mmHg increase in systolic BP (SBP), risk of dementia was increased by 22% (95% confidence interval [CI] 1.15–1.30) in subjects aged 40–59 years and 8% (95% CI 1.04–1.11) in subjects aged 60–69 years. No significant associations were observed in subjects aged ≥ 70 years. Among subjects aged 40–59 years, both vascular and Alzheimer’s dementia risks were increased with increasing SBP. Increasing hypertension burden (proportion of days with increased BP) was associated with higher dementia risk (hazard ratio [HR] 1.09 per 10% increase, 95% CI 1.08–1.10). Among patients with baseline SBP ≥ 140 mmHg, optimal follow-up SBP (120–139 mmHg) was associated with decreased dementia risk (HR 0.69, 95% CI 0.50–0.95). Hypertension burden was associated with higher risks of dementia. Adequate BP control was associated with lower risk of dementia in individuals aged < 70 years.